Removal of Fe ion from polluted water by reusing spent coffee grounds - Mohamed @ Mohd Ramli, Khairul Nizam; Lee, Lai Yee (Universiti Putra Malaysia Press, 2019)
High concentration of iron (Fe) levels (above 1.0 mg/L) in water causes bad taste, staining and deposition in pipes and results in high turbidity in water supplies. Existing treatment technologies (which have been conventionally applied to remove Fe ions), are expensive and cause toxic sludge production. A set of experiments was carried out to evaluate the Fe uptake potential of spent coffee grounds by conducting batch tests in an aqueous solution through a biosorption process. Batch sorption studies were conducted based on pH, contact time, adsorbent dosage and adsorbent particle size. In addition, initial metal concentration was investigated. Flame atomic adsorption spectroscopy analysis revealed that the maximum adsorption recorded was 0.470 mg g-1 by using 0.30 g of 210-355 µm coffee with the maximum uptake percentage of Fe (92.9%) for 60 minutes at pH 4. Adsorption behavior of Fe ions on a surface of coffee grounds was well-interpreted by Langmuir model (R2 = 0.999). A kinetic study indicated that the Fe ions uptake was well-fitted by the pseudo second-order reaction model with good correlation (R2 = 0.993). The study offered an affirmative answer to the hypothesis of reusing eco-friendly and low-cost coffee grounds for removal of Fe ions from polluted waters.